Pengaruh Media Pembelajaran Audiovisual Dalam Bentuk Diktat Kartun Terhadap Hasil Belajar Siswa Dengan Mengontrol Kemampuan Numerik Siswa: The Influence of Cartoon-Based Audio Visual Learning Media On Student Learning Outcomes By Control Of Numeric Students - Edy Hermawan; I Gusti Agung Ngurah Trisna Jayantika; Ni Kadek Liska Andari (Emasains : Jurnal Edukasi Matematika dan Sains, 2019)
This study aims to determine the effect of audiovisual learning media in the form of cartoon dictates on mathematics learning outcomes by controlling the numerical abilities of students in class VII of SMP Negeri 1 Blahbatuh. In its implementation, the experimental group used audiovisual learning media in the form of cartoon dictates and control groups using conventional media. In accordance with the purpose of the research is to determine the effect of audiovisual learning media in the form of cartoon dictates on mathematics learning outcomes by controlling students' numerical abilities, then this type of research is quasi-experimental with non-equivalent post test only control group design. The population in this study were all students of class VII of SMP Negeri 1 Blahbatuh with a total of 387 students. The sample in this study was carried out by simple random sampling technique. There are two types of instruments for capturing data, namely numerical ability tests and tests of mathematics learning outcomes that were previously tested. Data obtained were then analyzed using t-test and anakova. The result of this study there are differences of mathematics learning result students using audiovisual learning media in cartoon diktat form with the conventional media before or after controlling numerical ability.